Application of the intelligent interactive system to promote the full course care of very low birth weight infants - Xie, Namei; Ye, Ruming; Chen, Yuying; Lin, Ying; Huang, Xianghui; Zhuang, Deyi (Frontiers in Pediatrics, 2025)
AimTo explore the effects of full course care with an intelligent interactive system on the growth, neurodevelopment and follow up adherence of very low birth weight infants (VLBW), as well as parental satisfaction.MethodsThe preterm infants admitted between January 2022 and December 2022 were designated as the experimental group, while those admitted from January 2021 to December 2021 constituted the control group. The experimental group received a full course of care through an intelligent interactive system, whereas the control group received inpatient and follow-up care from primary and clinic nurses, respectively. We compared the two groups' parental satisfaction at discharge, infants' anthropometric assessments, follow-up adherence, and infant's neurodevelopment.ResultsFrom January 1, 2021, to December 31, 2022, 171 VLBWI and their parents were enrolled at a tertiary hospital, with 89 infants in the experimental group and 82 in the control group. Parental satisfaction in the experimental group was significantly higher than in the control group (P < 0.05). At the corrected ages of 1, 3, and 6 months, the height and weight of the preterm infants in the experimental group were also superior to those of the control group (P < 0.05). Additionally, the follow-up adherence rate of the experimental group exceeded that of the control group at the corrected ages of 3 and 6 months (P < 0.05). Furthermore, at the corrected age of 6 months, the scores for fine motor skills, adaptability, and social interaction of infants in the experimental group were higher than those in the control group (P < 0.05).ConclusionAn intelligent interactive system can facilitate comprehensive management of VLBWI by integrating inpatient care and follow-up. This approach has significant clinical value as it promotes the physical and cognitive development of infants while enhancing parent satisfaction and adherence.